1999
DOI: 10.1115/1.429621
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Skeletal Muscle Properties in Cadaveric Test Specimens: Effects of Mechanical Loading, Postmortem Time, and Freezer Storage

Abstract: Investigators currently lack the data necessary to define the state of skeletal muscle properties within cadaveric specimens. The purpose of this study is to define the temporal changes in the postmortem properties of skeletal muscle as a function of mechanical loading and freezer storage. The tibialis anterior of the New Zealand white rabbit was chosen for study. Modulus and no-load strain were found to vary significantly from live after eight hours postmortem. Following the changes that occur during rigor mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(101 citation statements)
references
References 28 publications
1
94
0
2
Order By: Relevance
“…More importantly, Morrow et al, 2010 froze their samples within an hour of the animal sacrifice, but no effort was made to discuss the thawing process they used. Although it has been found that a freeze thaw cycle does not affect the post rigor response of muscle tissue (Van Ee et al, 2000), the thawing process remains an important part of their experiments as it is likely to have allowed rigor mortis to set in and make the tissue much stiffer (the rigor mortis characterisation investigation performed on freshly harvested porcine tissue (Van Loocke, et al,. 2006, showed that the testing window is two hours after death before rigor mortis starts influencing the passive response of porcine skeletal muscles).…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…More importantly, Morrow et al, 2010 froze their samples within an hour of the animal sacrifice, but no effort was made to discuss the thawing process they used. Although it has been found that a freeze thaw cycle does not affect the post rigor response of muscle tissue (Van Ee et al, 2000), the thawing process remains an important part of their experiments as it is likely to have allowed rigor mortis to set in and make the tissue much stiffer (the rigor mortis characterisation investigation performed on freshly harvested porcine tissue (Van Loocke, et al,. 2006, showed that the testing window is two hours after death before rigor mortis starts influencing the passive response of porcine skeletal muscles).…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…There is also a paucity of good quality research in human tissue properties due to difficulties in obtaining post-mortem human subjects and the degradation in properties associated with the conditions the body is kept post-mortem prior to testing (Van Ee et al, 2000) and storage conditions (Menz, 1971;Lee & Pelker, 1985;Clavert et al, 2001). Consequently, very few studies presented are of human tissues (Chawla et al, 2009;Balaraman et al, 2012).…”
Section: Structure and Composition Of Organic Muscle Tissuementioning
confidence: 99%
“…However, when performed on each experimental group, the multi linear regressions showed that up to 60% or 78% of E can be explained by the MRI parameters in the rigor mortis (Equation (2)) and post-rigor mortis (Equation (3)) groups respectively. The highest variance inflation factor (VIF) was attributed to ADC in Equation (1) and to MTR in Equation (2), suggesting that these parameters were likely candidates for elimination in the equations. However, in Equation (3), all the parameters presented equivalent VIFs.…”
Section: Multi Linear Regressionsmentioning
confidence: 99%
“…Even if the material properties vary greatly during rigor mortis [2], there was less than one hour between the MRI acquisition and the mechanical tests, leading to acceptable changes in the rigor mortis group between the two tests.…”
Section: Samples Preparationmentioning
confidence: 99%
See 1 more Smart Citation